Sanción o prevención. ¿Qué factor es más importante para la disminución del número de accidentes de tránsito y sus consecuencias en el cantón Loja en el periodo 2018-2021 - Idrobo Contento., Juan Carlos (2023)
Traffic accidents are the first cause of death for children between 5 and 14 years of age and the second for young people between 15 and 29 years of age. Worldwide, they generate around 1.35 million deaths as a social cost. Traffic accidents cost most countries 3% of their GDP, for which the present investigation arises where it will be analyzed through a statistical and econometric analysis, which factor is most important for reducing the number of traffic accidents? traffic and its consequences in the Loja canton in the period 2018-2021. This research examines the causal link between the number of traffic accidents, the number of people injured and killed with the number of citations for drunk drivers, the number of road safety campaigns, the number of operations, the number of vehicles and economic activity. circumstantial, in the Loja canton. For this, the methodology used includes an autoregressive model with distributed lags (ARDL) with a time series, to examine the long-term cointegration relationship between the variables. The results justify the existence of a long-term negative relationship, jointly between the citations variables and the number of traffic accidents, people injured and deceased. The short-term economic activity index and the number of vehicles, on the other hand, have a positive and statistically significant relationship with accidents and their consequences. The main conclusions are that the most efficient method to deal with this social problem is to increase the number of citations for drunk drivers, highlighting that sanctions are more influential than prevention. Finally, it is recommended to carry out an exclusive plan focused on progressively and significantly increasing the number of citations to drunk drivers.